Identification and Optimization Speed Control of BLDC Motor Using Fuzzy Logic Controller - Anshory, Izza; Robandi, Imam; ., Wirawan; ., . (International Journal of Engineering and Technology, 2018)
Better performance, such as speed of response, overshoot and steady state error on BLDC motors, needs to be improved continuously through optimization. The first method, is to design the hardware, take the current data, voltage and motor speed through measurement. The data obtained is simulated through the existing tools in Matlab to obtain the mathematical model in the form of transfer function. BLDC motor transfer function obtained, used as the basis for optimizing the fuzzy logic method. The results showed that the stability performance in BLDC motor speed control system showed an improvement after optimization using fuzzy logic.Â Â